Evaluation of testicular microlithiasis in varicoceles - Kobayashi, Hideyuki (Reprod Med Biol, 2002)
Background:  Testicular microlithiasis is said to be characterized by calcific concretions within the seminiferous tubules. There have been reports suggesting a link between testicular microlithiasis and testicular dysfunction and tumors. Methods:  In this study, we assessed subjects with varicoceles detected by using testicular ultrasound, and evaluated the cases of testicular microlithiasis in terms of age, seminalysis findings, and endocrinological parameters (testosterone, follicular stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL)). The subjects comprised 224 patients with varicoceles diagnosed by using testicular ultrasound, who attended this institution as outpatients between January 1998 and August 2000. Results:  Testicular microlithiasis was detected in 15 out of 224 subjects (6.7%), bilateral in all cases. No significant differences were seen between the group with testicular microlithiasis and the group without testicular microlithiasis, in terms of age, seminalysis findings, and/or endocrinological parameters (testosterone, FSH, LH, prolactin). The incidence of testicular microlithiasis in outpatients undergoing testicular ultrasound varies between reports, but is of the order of 0.6–2.0%. Conclusion:  In this study, we found a high proportion of testicular microlithiasis at 6.7%, strongly suggesting a link with male infertility. (Reprod Med Biol 2002; 1: 75–79)